A CRITICAL REVIEW ON GUILLAIN BARRE SYNDROME (ACUTE INFLAMMATORY DEMYELINATING POLYNEUROPATHY- AIDP) AND THEIR MANAGEMENT (International Journal of Ayurveda and Pharma Research, 2020)
Guillain- Barre Syndrome is serious health problem, that occurs when the body`s defence system mistakenly attacks parts of the nervous system. In about 50% of people with these syndrome symptoms begin about 5 days to 3 weeks after a mild infection symptoms include weakness and pin and needle sensation or loss of sensation. It is form of polyneuropathy that cause one episode of increasing muscle weakness. Weakness is more prominent than abnormal sensation reflex. Usually weakness begins both legs and moves up the body. In GBS, the body`s immune system attacks the myelin sheath which surround the axon of many nerves and enable nerve impulses to travel quickly. It may lead to life threatening complication in particular if respiratory muscles are affected or if the autonomic nervous system is involved. Worldwide, the annual incidence is about 0.6- 4.0 occurrences per 1,00,000 people. Electromyography and nerve conduction studies can help confirm the diagnosis. Plasmapheresis or immunoglobulin given intravenously may speed recovery. GBS as such is not correlated with any disease which is described in Ayurveda but pathology of GBS is Vata dominating disorder along with association of Pitta and Kapha dosha. As a precipitating factor produced functions of GI biofire plays an important role by producing Ama like reactive species in genesis of this disease. So at the management of GBS through Ayurveda anti-Vata and anti-Ama measures kept in mind while prescribing the drug.